Proving discriminatory violence at the European Court of Human Rights - Mačkić, Jasmina, 1984- (Leiden studies on the frontiers of international law ;, 2018)
"In 'Proving Discriminatory Violence at the European Court of Human Rights' Jasmina Mackic unveils the evidentiary issues faced by the European Court of Human Rights when dealing with cases of discriminatory violence. In that context, she evaluates the Court's application of the standard of proof 'beyond reasonable doubt' and aims to answer the question whether that standard forms an obstacle in establishing the occurrence of discriminatory violence. In addition, she offers an assessment into the circumstances in which the burden of proof may shift from the applicant to the respondent state. The author also looks at the types of evidentiary materials that may be used by the Court in order to establish discriminatory violence."